Assessment of Farmer-Led Irrigation Development in Niger - Soumaila, Amadou (World Bank, Washington, DC, 2021)
Niger is a large landlocked country whose northern two-thirds lies within the Sahara Desert with a population of about 21.5 million people. Most of the population is concentrated in areas around the Niger River in the southwestern corner of the country and along its long southern border with Nigeria. Niger’s economic activity is concentrated on traditional activities, primarily agriculture, livestock, forestry, and fishery but also informal trade and production. The country has experienced declining average rainfall, desertification, recurring droughts, and deforestation. Undernourishment is widespread. Agricultural risks, primarily droughts in Niger, have severe economic consequences with wide repercussions. Farmer-led irrigation (FLI) in the Niger context could be defined as irrigation privately owned and managed by farmers. The purpose of this study is to analyze the extent and the environment of FLI development in Niger, the challenges and constraints, and the business opportunities to be piloted.